Change in endothelial function state under the influence of antihypertensive therapy in patients with arterial hypertension and high cardiovascular risk. - Turlyun, T. S. (Medicni Perspektivi, 2014)
The article analyzes the indicators characterizing endothelial function in patients of distinguished groups at the initial stage of the study (visit 1) and during the treatment (visit 2). At baseline levels of endothelin-1 in the blood of patients of all groups did not differ significantly between the groups distinguished. After treatment, the dynamics of the indicator in all groups was positive and statistically significant (p<0,05): the level of ET-1 in the group with HD decreased by 7,7%, more pronounced changes were observed in hypertensive patients with type 2 diabetes - indicator decreased by 21,7% (p<0,05), testifying to reducing of endothelin-1 formation and its entering to the blood.When comparing control and treatment groups (0,37±0,06 fmol/ml) a twofold excess of endothelin-1 in hypertensive groups (p<0,01) and in patients with hypertension and diabetes mellitus type 2 (p<0,01) was observed. After the treatment with losartan potassium and hydrochlorothiazide, a statistically significant reduction of ET-1 in the group without hypertension comorbidity (p<0,004) and in the group of hypertensive type 2 diabetic (p<0,004) was noted. Dynamics of ET-1 decrease in the group with type 2 diabetes, but statistically unreliable (p<0,233) was noted. Under the influence of losartan potassium and hydrochlorothiazide average albuminuria level decreased in groups of patients with hypertension and hypertension with type 2 diabetes (p<0,05). In patients with type 2 diabetes who were not taking antihypertensive drugs, the rate did not change (p>0,60).